Crosstalk between SARS-CoV-2 and the angiotensin system: Clinical implications - Safa Kinaneh; Shadi Hamoud; Yara Knany; Samuel N. Heyman; Zaid Abassi (American Journal of Physiology-Cell Physiology, 2026)
ACE2, serving as a receptor to SARS-CoV-2, is a key player in RAAS. Consequent ACE2 depletion disrupts the balance between the Ang II/ AT1R and Ang (1-7)/MasR arms of the angiotensin system, promoting intense inflammation. A crosstalk existing between the angiotensin system and ACE2/spike proteins may affect the infection severity, with potential therapeutic implications. Evaluating such potential interactions and their relevance to the severity of COVID-19, which is directly affected by ACE2 abundance or indirectly by RAAS axis dysregulation. The intensity of SARS-CoV-2 infection was assessed using a cell-to-cell fusion assay and AT1R activation was assessed using AT1R-Tango approach. We demonstrate the critical function of ACE2 in mitigating AT1R activation, which is disrupted following SARS-CoV-2 infection. Moreover, we show that the spike protein indirectly intensifies AT1R activation. Beyond its established role in activating MasR, Ang1-7 was found to function as a biased agonist for AT1R, without altering ACE2 levels or affecting SARS-CoV-2 entry. In contrast, AVE0991, a MasR agonist, was observed to increase ACE2 levels and enhance SARS-CoV-2 infection. Angiotensin receptor blockers (ARBs) effectively inhibited AT1R activity and had minimal impact on viral entry. Our data supports the likelihood that AT1R blockers (ARBs) may be effective in managing COVID-19 since they inhibit AT1R activation and its deleterious subsequent effects, with no impact on SARS-CoV-2 entry. By contrast, MasR and its agonist AVE0991, by increasing ACE2 levels, may restore RAAS physiological balance, but facilitate host cell invasion by SARS-CoV-2.